EFFECTIVE PUBLIC SPEAKING TRAINING FOR YOUTH ORGANIZATIONS IN ARJASARI VILLAGE - Anartia, Niki; Amaretha, Riska; Meltareza, Ridma (Universitas INABA, 2022)
An organization is a place or place to collect ideas, thoughts, and even ideas to achieve a goal that is designed together. In this case, it is necessary to have internal communication between members of the organization itself. It is also necessary to disseminate information to audiences in an effective way so that the message conveyed can be received easily. In a village, a community organization becomes a beacon for residents in fostering and developing to realize organizational goals. Here the ability to speak in public (public speaking) is needed so that the message conveyed can be well received. Therefore, organizing public speaking training (public speaking) so that members of the organization are accustomed to speaking in public properly so that the intended message can be easily understood without any misunderstandings.